Strategi Dakwah dalam Pembinaan Ketauhidan Narapidana di Lapas Kelas 1 Sukamiskin - Ifa Ulyatusyarifa; Komarudin Shaleh; Nandang HMZ (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. Islamic da'wah is one of the duties of carrying out Islamic da'wah as the responsibility of all Muslims. Islamic da'wah is an obligation among various religious obligations. This study discusses the Da'wah Strategy in Fostering Unity of Convicts in Class 1 Sukamiskin Correctional Institution. With the formulation of the problem: (1) What is the Da'wah Strategy in Fostering Unity of Convicts in Class 1 Sukamiskin Correctional Institution? (2) What are the supporting factors in fostering the Unity of Prisoners in Class 1 Sukamiskin Prison? (3) What are the Obstacles in Fostering the Unity of Prisoners in Class 1 Sukamiskin Prison The research method used by the author is a qualitative research method. data collection techniques were carried out by means of observation to determine the condition of the object directly, this interview was used with the aim of obtaining data clearly and concretely in accordance with the object, the documentation carried out consisted of several pictures of the Correctional Institution and photographs related to the research. The results of the study: A Da'wah Strategy that is used in coaching prisoners in Correctional Institutions, namely, oral da'wah, written da'wah, and action da'wah. Efforts in fostering the Unity of Prisoners. Abstrak. Dakwah Islam merupakan salah satu tugas kewajiban melaksanakan dakwah Islam sebagai tanggung jawab seluruh umat Islam. Dakwah Islam adalah kewajiban di antara berbagai kewajiban yang religius. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kualitatif, Adapun tujuan dan manfaat penelitian ini adalah mengetahui bagaimana strategi dakwah yang di terapkan Lapas kelas 1 sukamiskin kepada Narapidana serta faktor pendukung dan penghambat. Sumber data dalam penelitian ini adalah Pegawai Rutan, Narapidana dan Pembimbing Narapidana, metode dalam pengumpulan data adalah observasi, wawancara, dokumentasi. Penelitian ini membahas tentang Strategi Dakwah Dalam Pembinaan Ketauhidan Narapidana Di Lembaga Pemasyarakatan Kelas 1 Sukamiskin. Dengan rumusan masalah: (1) Bagaimana Strategi Dakwah Dalam Pembinaan Ketauhidan Narapidana Di Lembaga Pemasyarakatan Kelas 1 Sukamiskin ? (2) Apakah faktor pendukung dalam Pembinaan Ketauhidan Narapidana Di Lapas Kelas 1 Sukamiskin ? (3) Apa Hambatan dalam Pembinaan Ketauhidan Narapidan di Lapas kelas 1 Sukamiskin. Hasil dari penelitian ini menunjukkan bahwa strategi dalam pembinaan ketauhidan narapidana efektif mencakup dalam bidang aqidah, syari’ah dan akhlak.